2008
DOI: 10.1002/lt.21396
|View full text |Cite
|
Sign up to set email alerts
|

Steroid avoidance in liver transplantation: Meta-analysis and meta-regression of randomized trials

Abstract: Steroid use after liver transplantation (LT) has been associated with diabetes, hypertension, hyperlipidemia, obesity, and hepatitis C (HCV) recurrence. We performed meta-analysis and meta-regression of 30 publications representing 19 randomized trials that compared steroid-free with steroid-based immunosuppression (IS). There were no differences in death, graft loss, and infection. Steroid-free recipients demonstrated a trend toward reduced hypertension [relative risk (RR) 0.84, P ϭ 0.08], and statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
5
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 41 publications
4
114
5
6
Order By: Relevance
“…However there is a lack of robust data showing the efficacy of this approach. A meta-analysis of 13 trials [100] showed that steroid avoidance was associated with lower HCV recurrence (RR = 0.90, P = 0.03), although no individual trial reached statistical significance. The heterogeneity, short-term follow-up and relatively small size of many of the trials, as well as the lack of information on steroid dosage, make conclusions less robust.…”
Section: Post-transplant Immunosuppressionmentioning
confidence: 99%
“…However there is a lack of robust data showing the efficacy of this approach. A meta-analysis of 13 trials [100] showed that steroid avoidance was associated with lower HCV recurrence (RR = 0.90, P = 0.03), although no individual trial reached statistical significance. The heterogeneity, short-term follow-up and relatively small size of many of the trials, as well as the lack of information on steroid dosage, make conclusions less robust.…”
Section: Post-transplant Immunosuppressionmentioning
confidence: 99%
“…57,58 There is no compelling evidence that avoiding steroids in the early postoperative period results in improved long-term outcomes; however, a recent meta-analysis noted a potential decrease in risk of HCV recurrence and cytomegalovirus infection. 59 Pulsed steroid treatment for acute cellular rejection was found, not only to be associated with transient 1-to 2-log increases in HCV RNA levels 60 ; but also, increased mortality and graft loss in this subset of recipients. 61 In a prospective randomized controlled study of 495 recipients with HCV infection, no difference was seen in the histologic recurrence rate of hepatitis C at 12 months after transplant between patients receiving cyclosporine versus tacrolimus.…”
Section: Lines Of Managementmentioning
confidence: 94%
“…All of these effects will contribute to higher HCV levels in the first instance and potential HCV cytopathic injury. Two meta-analyses have shown less severe HCV recurrence in CS-free protocols [12,13]; however, a large RCT showed no benefit of steroid-free IS in terms of allograft rejection, HCV recurrence or patient or graft survival [14].…”
Section: Exception 2: Hcv Infectionmentioning
confidence: 99%
“…Meta-analyses have demonstrated a reduction in hypertension and diabetes with steroid-free IS [12,13]. Furthermore, it is well recognized that tacrolimus therapy increases the risk of diabetes [1].…”
Section: Exception 3: Hepatocellular Carcinomamentioning
confidence: 99%